Rynek pracy w Polsce z perspektywy osób z uszkodzeniem słuchu - Krawczyk, Julia (Zeszyty Naukowe Pedagogiki Specjalnej, 2022)
A job opportunity is an essential aspect of everyday life for everyone. Unfortunately, this topic is often overlooked in the context of people with hearing damage. The article aims to provide an overview of the situation of the hard of hearing and deaf people on the labor market in Poland. The definition of the labor market and the medical classification of people with hearing damage will be presented. Professional activity, perception of work by people with hearing damage and social relations in the work environment will be analyzed.